2008
DOI: 10.3132/dvdr.2008.043
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the vascular and pleiotropic effects of atorvastatin and pioglitazone in a population at high cardiovascular risk

Abstract: Key words: atherosclerosis, inflammation, intima-media thickness, PPARγ, statins. IntroductionAtherosclerosis is a complex process that progresses through various functional and morphological alterations in the vessel wall, cumulating in overt cardiovascular disease. Measurement of the intima-media thickness (IMT) of the common carotid artery (CCA) by ultrasound has been established as a reliable screening tool for atherosclerosis and has been shown to predict the risk for stroke and ischaemic heart disease.1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 34 publications
(60 reference statements)
4
29
0
Order By: Relevance
“…The combination of ATOR + PIO or other statins and thiazolidinediones has shown synergic interactions towards the treatment and prevention of cardiovascular illnesses and diabetes through diverse experimental models (Forst et al, , 2008Hanefeld et al, 2007). Our results showed that ATOR+PIO inhibited proliferation of lung mucoepidermoid carcinoma; other studies also reported the anticancer effect of HMG-CoA inhibitor and PPARγ agonist in lines of lung cancer (Li et al, 2010;Chen et al, 2012Chen et al, , 2013.…”
Section: Discussionsupporting
confidence: 66%
“…The combination of ATOR + PIO or other statins and thiazolidinediones has shown synergic interactions towards the treatment and prevention of cardiovascular illnesses and diabetes through diverse experimental models (Forst et al, , 2008Hanefeld et al, 2007). Our results showed that ATOR+PIO inhibited proliferation of lung mucoepidermoid carcinoma; other studies also reported the anticancer effect of HMG-CoA inhibitor and PPARγ agonist in lines of lung cancer (Li et al, 2010;Chen et al, 2012Chen et al, , 2013.…”
Section: Discussionsupporting
confidence: 66%
“…Indeed, studies have demonstrated that pioglitazone therapy benefits individuals with elevated hs-CRP values. [46][47][48][49][50][51][52][53] 54 published data of 136 Japanese type 2 diabetes patients showing that pioglitazone treatment (30 mg daily for 3 months) significantly reduced hyperglycemia and hs-CRP relative to an untreated control group. In fact, a stratification into glycemic control responders [>1% of reduction in hemoglobin A1c (HbA1c)] and nonresponders revealed that CRP reduction with pioglitazone occurred independently of changes in parameters related to glucose metabolism.…”
Section: Effects Of Pioglitazone Treatment On Hs-crp Reductionmentioning
confidence: 99%
“…57 Our own investigations examined insulinsensitizing effects on CRP levels compared to the impact of lipid-lowering and antihypertensive therapy in patients at increased macrovascular risk. 47,49,53 The PIOSTAT study demonstrated that nondiabetic patients with vascular insulin resistance and dyslipidemia treated with pioglitazone therapy experienced an overall reduction in chronic systemic inflammation, which was significantly more pronounced than with alternative simvastatin therapy. Giving both drugs in combination resulted in a synergistic effect on the inflammatory biomarker hs-CRP.…”
Section: Effects Of Pioglitazone Treatment On Hs-crp Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was not the case with other more commonly prescribed drugs for treatment of metabolic syndrome such as metformin or sulfonylurea drugs. [24][25][26][27] These findings indicate that a more individualized approach to diabetes therapy may provide a better way to improve the macrovascular prognosis and outcome for a given patient. Characterization of the individual risk situation of patients by means of hs-CRP and other biomarkers (e.g., adiponectin to assess the activity of the visceral adipose tissue and the related insulin resistance 28 or intact proinsulin to determine the degree of β-cell dysfunction 29 ) may allow for selection and monitoring of more individually tailored therapies.…”
Section: Discussionmentioning
confidence: 94%